2018
DOI: 10.1101/403881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-Specific Protection Against Diet-Induced Non-Alcoholic Fatty Liver Disease in TRPV1 Null Mice

Abstract: ObjectivesTRPV1 channels have been linked to the development and progression of diabetes at multiple levels, including control of appetite and weight, regulation of pancreatic function, thermogenesis, metabolism and energy homeostasis. Despite this, little information is known regarding its role in liver homeostasis and nonalcoholic fatty liver disease (NAFLD).Methods and ResultsTo better understand the role of TRPV1 in liver metabolism, we explored the effects of a high fat/sugar diet (Western, 24-week regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In apolipoprotein E-deficient mice, evodiamine significantly reduced atherosclerosis, hyperlipidemia, and systemic inflammation and this beneficially therapeutic effect was not seen in ApoE −/− mice that lack TRPV1 ( Wei et al, 2013 ), suggesting that TRPV1 curbs the development of atherosclerosis. A similar observation was shown by Connell et al (2018) who showed that loss of TRPV1 gene in western-fed mice caused higher hepatic triglycerides, cholesterol and free fatty acid levels than wild type (WT) mice and this effect was more obvious in males than in females ( Connell et al, 2018 ). Similarly, Baskaran et al (2021) found that TRPV1 deficient mice developed metabolic dysfunction.…”
Section: Role Of Trpv1 In Metabolic Syndrome Associated With Hyperlip...supporting
confidence: 77%
“…In apolipoprotein E-deficient mice, evodiamine significantly reduced atherosclerosis, hyperlipidemia, and systemic inflammation and this beneficially therapeutic effect was not seen in ApoE −/− mice that lack TRPV1 ( Wei et al, 2013 ), suggesting that TRPV1 curbs the development of atherosclerosis. A similar observation was shown by Connell et al (2018) who showed that loss of TRPV1 gene in western-fed mice caused higher hepatic triglycerides, cholesterol and free fatty acid levels than wild type (WT) mice and this effect was more obvious in males than in females ( Connell et al, 2018 ). Similarly, Baskaran et al (2021) found that TRPV1 deficient mice developed metabolic dysfunction.…”
Section: Role Of Trpv1 In Metabolic Syndrome Associated With Hyperlip...supporting
confidence: 77%
“…Decreased TRPV1 expression in mice has been found to protect against diet-induced obesity [ 78 ] and promotes oxygen consumption, fat oxidation, and locomotor activity [ 79 ]. In contrast, loss of the TRPV1 gene in Western-fed mice causes hyperlipidemia, and animals exhibit reduced locomotor activity with a more pronounced effect in males than in females [ 80 , 81 ]. TRPV1 agonists, such as vanilloids, capsaicin, and oxytocin, influence lipid metabolism, mainly by reducing lipid deposition.…”
Section: Discussionmentioning
confidence: 99%